SYNTHESIS OF NOVEL INDOLO[3,2-c]QUINOLINES; ETHYL 3-CHLORO-9,11-DIMETHOXY INDOLO[3,2-c]QUINOLINE-6-CARBOXYLATE - Tutik Dwi Wahyuningsih (Universitas Gadjah Mada, 2005)
β-Carboline and its derivatives are significant due to their pharmacological importance. The synthesis of indolo[3,2-c]quinolines as a benzo analog of β-carboline has been carried out via an oxime ether intermediate. Reaction of 2'-glyoxylic ester with hydroxylamine hydrochloride in the presence of sodium acetate afforded the oxime acetate in 82%. It was then treated with natrium and fluoro-2,4-dinitrobenzene in ethanol to give an orange solid of oxime ether acetate which is in subsequent treatment with a base yielded a pale yellow solid of indolo[3,2-c]carboline in 43%.